Development of the Kajoetangan Heritage Area in Malang City: Public Perception - Ilfiana Firzaq Arifin (Historia, 2027)
The Kajoetangan Heritage Area is one of the villages in Malang City, precisely on Jln. Gen. Basuki, Klojen. Heritage Kajoetangan is unique, which can be seen from its architecture which still maintains Dutch characteristics. In 2018, Kampoeng Heritage Kajoetangan began to be developed, which is an important part of developing cultural tourism in Malang City. This research aims to find out what the public's perception is regarding development in the Malang city heritage area. This research uses a qualitative approach. The data collection techniques used were interviews, observation and documentation. Meanwhile, the results of this research are about the community's perception and response to the tourism development carried out in the Kajoetangan heritage village area.